The long and winding road of digital distribution. Or: why the ECJ's UsedSoft decision is of no use to keysellers. Issue 1 (June 2018) - Lober, Andreas; Klein, Susanne; Groothuis, Florian
Abstract : The 2012 UsedSoft decision of the Court of Justice of the European Union ('ECJ') disrupted the digital distribution of computer programs. Since then, unauthorised sellers of product and game keys often try to utilise the UsedSoft ruling and its principles to justify the resale of key codes. Against this background, we will review the new developments in this area, taking into account recent court decisions in Germany, which are based on European Directives. Furthermore, the impact of the UsedSoft decision on the gaming sector, where game keys are often distributed in digital form only, will be examined. Since the ECJ in its Nintendo decision and the German Federal Supreme Court 'BGH') in its World of Warcraft I decision both considered video games to be hybrid products, we will discuss whether and to what extent the Software Directive 2009/24/EC and the InfoSoc Directive 2001/29/EC are applicable. We then apply the findings to the distribution models used in the gaming sector and examine their legality.